The Cape Diaries of Lady Anne Barnard 1799-1800, vols 1 and 2, M. Lenta, B. Le Cordeur (eds.) (Historia, 2021)
This latest collection of Lady Anne Barnard's writing consists of the previously unpublished and unrevised diaries she kept in the Cape between 1799 and 1800. Each of the Van Riebeeck Society publications covers a year of her reflections on life at the Cape. In this sense the diaries are a sequel to her published journals, The Cape Journals of Lady Anne Barnard 1797-1798, edited by A. M. Lewin Robinson with Margaret Lenta and Dorothy Driver, also published by the Van Riebeeck Society (Cape Town, 1994) and are also a companion to the letters she wrote to Henry Dundas, The Letters of Lady Anne Barnard to Henry Dundas, edited by A. M. Lewin Robinson and published by Balkema (Cape Town, 1973).
Keywords: Cape Journals of Lady Anne Barnard 1797-1798